Effect of age on the short- and long-term outcomes of patients undergoing curative liver resection for HCC. Issue 6 (June 2022) - Tan, Laura L.Y.; Chew, Valerie T.W.; Syn, Nicholas; Tan, Ek-Khoon; Koh, Ye-Xin; Teo, Jin-Yao; Cheow, Peng-Chung; Jeyaraj, Prema Raj; Chow, Pierce K.H.; Chan, Chung-Yip; Chung, Alexander Y.F.; Ooi, London L.P.J.; et al.
Abstract: Background: Few studies have evaluated the outcomes of curative liver resection (LR) in octogenarian patients, analysed cancer-specific survival (CSS) with HCC-related death or explored the age-varying effect of HCC-related death in elderly patients undergoing LR. We aim to determine the effect of age on the short and long-term outcomes of LR for HCC. Methodology: Between 2000 and 2018, 1, 092 patients with primary HCC who underwent LR with curative intent were retrospectively reviewed. The log-rank test and Gray's test were used to assess the equality of survivor functions and competing risk-adjusted cumulative incidence functions between patients in the three age categories respectively. Regression adjustment was used to control for confounding bias via a Principal Component Analysis. Quantile, Firth logistic, Cox, and Fine-Gray competing risk regression were used to analyse continuous, binary, time-to-event, and cause-specific survival respectively. Restricted cubic splines were used to illustrate the dose-effect relationship between age and patient outcomes. Results: The study comprised of 764 young patients (<70 years), 278 septuagenarians (70–79 years old) and 50 octogenarians (≥80 years). Compared to young patients, octogenarians had significantly lower 5-year OS(62.1% vs 37.7%, p < 0.001). However, there was no significant difference in 1-year RFS(73.1% vs 67.0%, p = 0.774) or 5-year CSS (5.4% vs 15.2%, p = 0.674). Every 10-year increase in age was significantly associated with an increase length of stay (p < 0.001), postoperative complications (p = 0.004) and poorer OS(p = 0.018) but not significantly associated with major complications (p = 0.279), CSS(p = 0.338) or RFS(p = 0.941). Conclusion: Age by itself was associated with OS after LR for HCC but was not a significant risk factor for HCC-related death.